Processing innovative products based on herbal plants to promote a healthy lifestyle - Yuniarti Falya; Fauzan Akbar Nur Ardianto; Rafid Maulana; Dinda Wibowo; Putri Anggraeni; Devita Alifa Soleha; Dede Rafi Gifari; Nok Endang; Nur Amira Safitri; Lafarrel Dhany Maullah (Community Empowerment, 2023)
The collaborative community service in Pegagan Village, Palimanan District, Cirebon Regency, was implemented to address the issue of low public awareness about health, leading to challenges in providing balanced nutrition to children, maintaining family health, and the relatively low utilization of herbal products. The goal of this service program is to introduce and optimize the potential of local herbal plants as environmentally friendly and affordable product innovations. The service method involves socializing and demonstrating innovative products based on herbal plants, and the evaluation is conducted using a questionnaire. Based on the results obtained, post-socialization knowledge of local herbal product innovations increased, including awareness of the health benefits of emprit ginger (55.55%) and the production of emprit ginger granules (83.33%).